Effect of Inclination on Efficiency of Heat Pipe - Kabnure, Bahubali B.; Patil, Rajkumar.D. (Asian Review of Mechanical Engineering, 2017)
Heat pipes are used in several applications, where one has limited space and the necessity of a high heat flux. Of course it is still in use in space applications, but it is also used in heat transfer systems, cooling of computers, cell phones and cooling of solar collectors. Especially for micro applications there is micro heat pipes developed as for cooling the kernel of a cell phone down. Due to limited space in personal computers and the growing computational power it was necessary to find a new way to cool the processors down. By means of a heat pipe it is possible to connect the processor cooling unit to a bigger cooling unit fixed at the outside to cart of the energy. In this paper, different tests were carried out at the different angle of inclination of heat pipe having same current and voltage. The efficiencies at each angle of inclination are calculated from the obtained data.